Reframing SU(1, 1) Interferometry. Issue 11 (25th March 2020) - Caves, Carlton M.
Abstract: SU(1, 1) interferometry, proposed in a classic 1986 paper by Yurke, McCall, and Klauder, involves squeezing, displacing, and then unsqueezing two bosonic modes. It has, over the past decade, been implemented in a variety of experiments. Here, SU(1, 1) interferometry is taken apart, to see how and why it ticks. SU(1, 1) interferometry arises naturally as the two‐mode version of active‐squeezing‐enhanced, back‐action‐evading measurements aimed at detecting the phase‐space displacement of a harmonic oscillator subjected to a classical force. Truncating an SU(1, 1) interferometer, by omitting the second two‐mode squeezer, leaves a prototype that uses the entanglement of two‐mode squeezing to detect and characterize a disturbance on one of the two modes from measurement statistics gathered from both modes. Abstract : SU(1, 1) interferometry involves squeezing, displacing, and then unsqueezing two bosonic modes. It is the two‐mode version of active‐squeezing‐enhanced, back‐action‐evading measurements aimed at detecting a phase‐space displacement. A truncated SU(1, 1) interferometer uses the entanglement of two‐mode squeezing to detect and characterize a disturbance on one of the two modes from measurement statistics gathered from both modes.